Application of high resolution melting (HRM) analysis in detection of PDGFRA gene mutations among chronic myeloid leukemia patients treated with imanitib mesylate - Rashid, Nur Sabrina Abd (2020)
A molecular detection of PDGFRA variants is highly relevant for prognosis and therapy prediction in chronic myeloid leukemia (CML) patients treated with Imatinib mesylate (IM). Even though IM has shown an excellent efficacy as a frontline treatment in CML, emerging of resistance towards IM in some CML patients has become a major concern. The development of resistance can be either due to BCR-ABL dependent mechanism or BCR-ABL independent mechanism. The BCR-ABL independent mechanisms include factor in pharmacokinetics of IM such as absorption and distribution of metabolism. However, resistance to IM can also due to the involvement of others IM targeted tyrosine kinases that may play a role in the IM resistance. In response to growing demand for reliable, faster and more sensitive methods, the present study used a High resolution melting (HRM) analysis to elucidate the BCR-ABL independent mechanism involving PDGFRA tyrosine kinase, in Malaysian CML patients undergoing IM therapy. A total of 86 CML patients on IM therapy (43 IM resistances and 43 IM responses) were included in this study. Using HRM analysis, 86 CML patients were screened for PDGFRA variants of exon 10 (c.1432 T>C), exon 12 (c.1701 A>G), exon 14 (c.1977 C>A) and exon 18 (c.2525 A>T). The selected samples with showing different melting curve profile from the reference genotype was subjected to DNA sequencing analysis to validate the genotype. From the data analysed, two PDGFRA variants were detected in exons 10 and 12. The established HRM profile has demonstrated 100% sensitivity and specificity when compared to DNA sequencing. PDGFRA exon 10 (c.1432 T>C) showed a significant risk factor (OR 3.797; 95% CI: 1.502 – 9.591; p = 0.005) for the development of IM resistance. PDGFRA exon 12 (c.1701 A>G) was not a significant risk factor (OR 1.597; 95% CI: 0.681 – 3.745; p = 0.281) for IM resistance. However there was no PDGFRA heterogeneity detected for both exon 14 c.1977 C>G and exon 18 c.2525 A>T. The results suggested that PDGFRA influenced IM resistance in CML patients and further analysis are warranted to confirm the role of PDGFRA in IM resistance mechanism in CML patient.